Antibiotic-prescribing and antibiotic-resistance patterns among elderly citizens residing in two Nordic regions. Issue 4 (2nd April 2020) - Hansen, Matilde Bøgelund; Arpi, Magnus; Hedin, Katarina; Melander, Eva; Hertz, Frederik Boëtius; Thorsted, Anne Bonde; Jakobsen, Helle Neel; Hyllebusk, Lena; Brogaard, Emma; Jensen, Jette Nygaard
Abstract: Objective: The objective of this study was to compare antibiotic-prescribing rates in 2016 and antibiotic-resistance rates in 2017 among citizens aged ≥85 years between the Capital Region in Denmark and the Skåne Region in Sweden, with regards to overall antibiotic use and antibiotics of choice for urinary tract infections (UTIs) and skin and soft tissue infections (SSTIs). Methods: Inhabitants ≥85 year old on the date of prescription during 2016 and residing in the Capital Region or the Skåne Region were included for antibiotic-prescription analyses. Samples from 2017 from residents of the same regions who were ≥85 years old were included for antibiotic-resistance analyses. Antimicrobial use was determined according to the drugs of choice for UTIs and SSTIs in Denmark and Sweden. Students t -tests were used to compare antibiotic prescribing while a Chi-Squared test was performed to compare antibiotic resistance. Results: There was a significantly higher overall prescription rate among citizens ≥85 years in the Capital Region than in the Skåne Region. The same pattern was evident for the antibiotics of choice for UTIs and SSTIs except for clindamycin. Antibiotic resistance against all antibiotics included was more prominent in the Capital Region than in the Skåne Region. Conclusion: Considerable variation in antibiotic prescribing and resistance exists among elderly citizens between these two adjacent Nordic regions. Information and reflection on current practices and resistance patterns may direct attention towards antimicrobial stewardship as a higher priority and may help inform and motivate prescribing behaviours.